Bagea Product Development Analysis in UD. Baruasa Membiri Kendari City Using Quality Function Deployment (QFD) Method - Ikram Ikram; Sarinah Sarinah; Yusna Indarsyih (Jurusan Ilmu dan Teknologi Pangan, Fakultas Pertanian,, 2022)
This study aims to determine consumer satisfaction with the development of bagea product quality at UD. Baruasa left Kendari City using the Quality Function Deployment (QFD) method. Determination of the research location is done purposively. Data were collected by interview and documentation methods. The analytical method used is Quality Function Deployment (QFD). The results showed the development of bagea product quality at UD. Baruasa Membiri using the QFD method, it was found that the priorities for development by the wishes and needs of the customers were: (1) information on the nutritional value of bagea product packaging (8.70%), (2) variants of bagea product types (8, 25%), (3) attractive packaging design for bagea products (7.78%), (4) affordable selling prices for bagea products (7.15%), (5) there are promotional media (7.12%), (6 ) price compatibility with bagea product quality (6.39%), (7) no use of hazardous materials (6.36%),(8) bagea product texture (6.27%), (9) bagea product halal certificate and label (6.16%), (10) bagea product taste (6.07%), (11) special price for certain purchases of bagea products (6.05%), (12) bagea product quality (6.01%), ( 13) color of bagea products (5.95%), (14) expiration information (expiration date) (5.89%), and (15) ease of getting bagea products (5.79%).